Advanced feature based digital video stabilization - Spampinato, Giuseppe; Bruna, Arcangelo Ranieri; Guarneri, Ivana; Tomaselli, Valeria (2016 IEEE 6th International Conference on Consumer Electronics - Berlin (ICCE-Berlin), 2016)
The present paper describes a low-cost algorithm for video stabilization. Like other feature based algorithms, it is robust to motion blur, noise and illumination changes. Moreover, maintaining real time processing, it is not negatively affected by moving objects in the scene, works fine even in conditions of low details in the background and it is robust to scene changes.